Effects of calcining temperatures of Eu2+ and Dy3+ ion-codoped calcia-alumina binary compounds on their phase transition and luminescence properties - Liang, Chen-Jui; Siao, Hao-Yi (Materials chemistry and physics, 2017)
In this study, phase evolution as a function of calcining temperature in calcia-alumina binary compound phosphors was examined to interpret their luminescence properties. The binary compounds were prepared through a coprecipitation method employing potassium carbonate as the precipitant to obtain precursors with a high-precision stoichiometric composition for the calcination. The results indicate that the morphology, surface properties, and infrared transmittance of the prepared phosphors were affected by the calcining temperature. X-ray diffraction analysis results enabled identification of Ca12Al14O33, CaAl2O4, and CaAl4O7 phase transitions at various calcining temperatures. The amount of the CaAl2O4 phase increased with the calcining temperature within the range of 700–1060 °C. The Ca12Al14O33 and CaAl4O7 phases exhibited trends opposite to that of the CaAl2O4 phase. When the calcining temperature reached 980 °C, the CaAl2O4 phase (60.5%) was determined to be the main phase in the structure, and excellent emission intensity at an emission band of 449 nm was observed as a result of the complete substitution of Eu2+ for Ca2+. The emission intensity corresponding to Eu2+ 4f65d1 → 4f7 decreased slightly when the temperature reached 1060 °C because of more monoclinic reciprocal CaAl4O7 phase (81.5%) formation, causing the transfer of some Eu2+ to Eu3+, during which strong photoluminescence spectra of Eu3+5D0 → 7Fj (j = 0, 1, 2, 3, 4) within the wavelength range of 570–720 nm were observed. Because the strong photoluminescence spectra of the Eu2+ and Eu3+ emissions were together within the wavelength range of 449–720 nm in this phosphor, the photoluminescence was white light. One moderately intense emission band in the infrared region was observed and attributed to the Dy3+4F9/2 → 6Hj (j = 11/2, 13/2, 15/2) transition when the temperature was higher than 900 °C. Finally, the energy transitions of Eu2+, Eu3+, and Dy3+ and the nephelauxetic effect and crystal field are discussed. •Investigate the phases in crystallization stage of calcia-alumina binary system.•Describe the effect of phases in structure on the luminescence properties.•Depict the mechanism of white light photoluminescence.•Construe the energy levels for electron transitions of the Eu2+, Eu3+, and Dy3+.